BTK Inhibitors in Chronic Lymphocytic Leukemia: Biological Activity and Immune Effects - Palma, Marzia; Mulder, Tom A.; Österborg, Anders (Frontiers in Immunology, 2021)
Bruton´s tyrosine kinase (BTK) inhibitor (BTKi)s block the B-cell receptor (BCR) signaling cascade by binding to the BTK enzyme preventing the proliferation and survival of malignant and normal B cells. During the past decade, the clinical use of BTKis for the treatment of B-cell malignancies has exponentially grown, changing the treatment landscape for chronic lymphocytic leukemia (CLL) in particular. At present, three different covalent BTKis, ibrutinib, acalabrutinib and zanubrutinib, are FDA-approved and many new inhibitors are under development. Despite having remarkable selectivity for BTK, the first-in-class BTKi ibrutinib can also bind, with various affinities, to other kinases. The combined inhibition of BTK (“on-target” effect) and other kinases (“off-target” effect) can have additive or synergistic anti-tumor effects but also induce undesired side effects which might be treatment-limiting. Such “off-target” effects are expected to be more limited for second-generation BTKis. Moreover, the blockade of BCR signaling also indirectly affects the tumor microenvironment in CLL. Treatment with BTKis potentially impacts on both innate and adaptive immunity. Whether this affects infection susceptibility and vaccination efficacy requires further investigation. Here, we summarize the available knowledge on the impact of BTKis on the immune system and discuss the possible clinical implications. Indeed, a deeper knowledge on this topic could guide clinicians in the management and prevention of infections in patients with CLL treated with BTKis.